Web-Based Heart Disease Diagnosis System With Forward Chaining Method (Case Study Of Ibnu Sina Islamic Hospital) - Refni Wahyuni; Yuda Irawan (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2019)
Expert systems are computer-based applications that are used to solve problems thought by experts. The benefits of expert systems are to find solutions to problems that occur in various fields including medicine and medical. The problem that often occurs is the problem of public knowledge of the initial problems of heart disease and the lack of public attention to heart health. From this problem, the writer wants to raise the title